Application of dimensional analysis in economics - Grudzewski, Wiesław (IOS Press, 2013)
The modeling of economic phenomena and processes, in terms of their static and dynamic features and with regard to the characteristics of their course, is a major methodological trend in studies of the nature, properties and functioning of contemporary management systems. Models describing management systems must be of a multi-aspect nature, entailing aspects such as technical, economic and sociological factors on the one hand, and forecasting, planning, leading, controlling etc., on the other. Developing a method for incorporating such diverse data into a system of analysis is, needless to say, a complex process. Dimensional analysis is a tool which might be useful in this process, but one which, up to now, has been little explored in the economic sciences. This book explores the application of dimensional analysis in the field of economics. It has been structured in a way which corresponds to the formulation of economic quantities, and is divided into five sections: measuring of economic quantities, modeling of economic processes, principles of dimensional analysis, building of quantified dimensional models, and experiment and practical verification.